Meter-scale heterostructure printing for high-toughness fiber electrodes in intelligent digital apparel - Gun-Hee Lee; Yunheum Lee; Hyeonyeob Seo; Kyunghyun Jo; Jinwook Yeo; Semin Kim; Jae-Young Bae; Chul Kim; Carmel Majidi; Jiheong Kang; Seung-Kyun Kang; Seunghwa Ryu; et al. (Nature Communications)
Abstract Intelligent digital apparel, which integrates electronic functionalities into clothing, represents the future of healthcare and ubiquitous control in wearable devices. Realizing such apparel necessitates developing meter-scale conductive fibers with high toughness, conductivity, stable conductance under deformation, and mechanical durability. In this study, we present a heterostructure printing method capable of producing meter-scale (~50 m) biphasic conductive fibers that meet these criteria. Our approach involves encapsulating deformable liquid metal particles (LMPs) within a functionalized thermoplastic polyurethane matrix. This encapsulation induces in situ assembly of LMPs during fiber formation, creating a heterostructure that seamlessly integrates the matrix’s durability with the LMPs’ superior electrical performance. Unlike rigid conductive materials, deformable LMPs offer stretchability and toughness with a low gauge factor. Through precise twisting using an engineered annealing machine, multiple fiber strands are transformed into robust, electrically stable meter-scale electrodes. This advancement enhances their practicality in various intelligent digital apparel applications, such as stretchable displays, wearable healthcare systems, and digital controls.